Penerapan Metode Moving Average untuk Mengurangi Fluktuasi Daya pada Sistem Pembangkit Hibrida - Ismail, Syaiful; Rachmildha, Tri Desmana; Hamdani, Deny (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2024)
Along with the increasing use of solar photovoltaic (PV) panel technology in hybrid generation systems, several challenges must be faced. Some of these challenges are PV power fluctuations that will impact the operation of the generating system. To overcome these challenges, in the framework of this research, the Moving Average method is applied to the energy storage system in the form of a battery to balance the power fluctuations generated by PV solar cells that are channelled into the existing power system infrastructure. The Moving Average is applied to smooth the actual output power of PV by utilizing the control system on the converter connected to the DC Bus and integrating it with the AC system in the form of the MHP system and load. Batteries aim to absorb and release power to balance the PV power output and refer to the battery reference power generated by the Moving Average Method. The simulation results show that the performance of power smoothing using the Moving Average method has a significant impact compared to the conditions before applying the Moving Average technique. Thus, there is an increase in smoothing accuracy, and the power on the DC bus achieves stability to be supplied to the AC system. The successful application of the Moving Average method is closely related to the battery energy storage system, especially the converter and control system used. By reducing fluctuations, the goal of the hybrid generation system to overcome the uncertainty of energy supply can be achieved.